Use of analgesics in professional soccer players: A systematic review - Thomas Zandonai; Juan José Lozano; Mónica Escorial; Ana M. Peiró (Elsevier, 2023)
Objective: Use of painkillers appears to have become a widespread issue in the sporting environment as athletes pursue successful pain relief during competitions. We conducted a systematic review on the prevalence of analgesics use in soccer, using literature from January 1980 to July 2021. Methods: The systematic review followed PRISMA guidelines. Studies were obtained from the Cochrane Library, PubMed, Scopus, and Web of Science (WOS) databases. In total, 213 articles were found where 14 were selected. The risk of bias was assessed using the NIH scale for prevalence studies and the PEDro quality scale for randomized control trials (RCTs). Results: Less than 3% of the literature were randomized studies (n=10 observational; n=4 double-blind trials) and only 2 studies included females. At least 54% of the research subjects consumed analgesic drugs during the course of their tournaments, and nearly half of them (39-67%) did so before each match, mostly in the form of non-steroidal anti-inflammatory drugs (NSAIDs) (15% of daily use). Conclusion: Given that short-term observational studies indicated high consumption of analgesics despite limited evidence of their pain control effectiveness, the question is raised whether this potential drug abuse affects the sexes at the same rates and in the same ways. Further investigation into these specific cohorts is needed.